A physics-based flow stress model for cutting simulation of additively manufactured Alloy 718 - Malakizadi, Amir; M'Saoubi, Rachid (CIRP Annals, 2025)
A dislocation-based flow stress model is proposed to describe the behavior of Alloy 718 fabricated using laser-based and electron-beam powder bed fusion methods. This physics-based model is adaptive to microstructural variations including the size and volume fraction of γ″ precipitates, crystallographic texture, grain size and the density of immobile dislocations. Coupled with data from thermodynamic and kinetic simulations, as well as insights from advanced characterization methods, this model provides a framework for assessing machinability of additively manufactured Alloy 718. The predicted cutting forces and chip shape parameters showed a good agreement with the corresponding measurements.
Keywords: Additive manufacturing; Cutting; Modeling